Herman Thorn court-martial proceedings - Thorn, Herman
Volume (138 pages) containing the proceedings of the court-martial (1816 March 4-30) of Thorn, purser in the U.S. Navy, for misallocation of funds; and pamphlets and other papers relating to disputes and duels between naval officers. Persons represented include Benjamin Williams Crowninshield.
U.S. naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Crowninshield, Benjamin Williams, -- 1772-1851.; United States. -- Navy -- Officers; Courts-martial and courts of inquiry -- United States; Dueling -- United States; Naval officers